PROBLEM OF DIVERSE CONTEXTS AND SPEAKERS ABOUT GOD - Sj, Ignatius Jesudasan (Journal of Dharma, 2012)
Only believers can engage in meaningful God-talk in a variety of contexts. But the belief and its meanings and purpose would vary with the context and the person engaged in the talk. Context connotes the time and location or social space of the speakers relative to us or any other audience, who are presumably inspired, instructed and edified or shaped into a community by that talk. The talk then is meant to teach us to continue the same so as to grow as a community in our turn. But our times and contexts differ. There is a time of remembrance and forgetfulness, reception and rejection, conflict and reconciliation, triumph and failure, joy and sorrow, thanks and self-denunciation, celebration and mourning. Such a variety implies the spontaneity of the change of feeling and meaning which inevitably takes place across socio-cultural-historical space and time in terms of continuity or break with the talk. In many a context, supported by a particular biblical hermeneutic or God-talk, gender diversity is hardly celebrated.